From Insight to Impact: How AI Tools Transform Managerial Practice in Czech Companies - Pawliczek, Adam; Žálčík, Tereza; Matula, Aneta (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This study investigates the practical applications of artificial intelligence (AI) in managerial work, with a focus on how tools such as large language models (LLMs) support the personal and professional development of managers. It explores how AI is used for decision-making, information analysis, and communication, and assesses its perceived impact on managerial knowledge, skills, and productivity. The research combines a comprehensive literature review with empirical data from a structured survey of 42 managers in Moravian companies, primarily in the Czech Republic. The study evaluates the frequency, purpose, and tools used in AI-assisted management practice. AI tools are frequently used by managers, especially for information summarization, meeting preparation, and text generation. ChatGPT (GPT-4) is the dominant tool, with most respondents reporting weekly or daily use. The majority perceive AI as beneficial, with an average Likert score of 7.86 regarding its positive impact on performance. Limitations include the localized sample, rapid research timeframe, and fast-paced AI evolution, which may affect long-term generalizability. The study offers practical insights into how AI enhances managerial routines and leadership development. This paper provides rare, localized empirical evidence on AI adoption in management, contributing to a fast-growing global research area.